2017
DOI: 10.2298/csis151101006t
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and implementation of IP and robust header compression schemes for TCP and UDP traffic in static and dynamic wireless contexts

Abstract: Modern cellular networks utilising the long-term evolution (LTE) set of standards face an ever-increasing demand for mobile data from connected devices. Header compression is commonly employed to minimise the overhead for IP-based cellular network traffic. In this paper, we evaluate the three header compression implementations used by these networks with respect to their potential throughput increase and complexity for different mobile service scenarios over wireless IP networks. Specifically, we consider head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The work was focused on the revenue and cost of radio resources. In a different approach, an evaluation of the three implementations of header compression was used by IP-based cellular network traffic [10]. It was observed that the compressed header savings typically range from 50 % to about 60 % for both RoHC versions and it is at 85 % for the IPHC with occasional uncompressed refreshes.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The work was focused on the revenue and cost of radio resources. In a different approach, an evaluation of the three implementations of header compression was used by IP-based cellular network traffic [10]. It was observed that the compressed header savings typically range from 50 % to about 60 % for both RoHC versions and it is at 85 % for the IPHC with occasional uncompressed refreshes.…”
Section: Related Workmentioning
confidence: 99%
“…Many other new generation technologies that are expected to be designed in this area of compression will be for mobile phones and IoT. The adoption of ROHC technique in modern android mobile devices, is becoming widespread [10]. ROHC technology will not increase power consumption and it has a potential of decreasing mobile battery drain by 0.05 Watt, when packet payloads are small [10].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations